The Effect of Internal Audit, and Utilization of Information Technology, on the Quality of Financial Statements With Internal Control System as a Moderating Variable - Herman Darwis; Yustiana Djaelani; Rizki Wahyu Utami Ohorella (Yayasan Riset dan Pengembangan Intelektual, 2023)
The purpose of this study was presented empirical evidence of internal audit and information technology impact on the quality of local government financial reports, with the government's internal control system serving as a moderating variable. Survey containing a questionnaire was used to collect data. Employees of the finance sector of the Regional Apparatus Organization of North Maluku Province comprised the study's population. Proportional random sampling was utilized as the samplimg technique. The SPSS application was used to perform simple linear regression analysis and multiple linear regression (Moderate Regression Analysis). The study's findings indicated that internal audit variables and the usage of information technology had an impact on the quality of financial reports. The internal control system did not mediate the relationship between internal audit, information technology utilization, and financial report quality. Internal audit and the usage of information technology should be expanded by regional governments since they have been shown to improve the quality of regional government financial reporting.